Stem Cell Processing [electronic resource] - Pham, Phuc Van.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This invaluable resource delineates procedures for development and use of stem cells in the laboratory and explores the potential for clinical applications. The text discusses mesenchymal stem cell isolation, isolation of adipose derived stem cells, new trends of induced pluripotent stem cells in disease treatment, cord blood banking, future directions of the discussed therapies and much more. The chapters are contributed by preeminent scientists in the field and present a comprehensive picture of stem cell processes, from development in the laboratory to effects and side-effects of clinical application. Stem Cell Processing and the other books in the Stem Cells in Clinical Applications series, edited by Dr. Phuc Van Pham, is essential reading for scientists, researchers, advanced students and clinicians working in stem cells, regenerative medicine or tissue engineering.
Preface -- 1. Stem Cell Therapy: Accepted Therapies and Managing the Hope of Society -- 2. Mesenchymal Stem Cells in Clinical Applications -- 3. Ageing and Senescence in Mesenchymal Stem Cells -- 4. New Trends in Clinic Applications of Induced Pluripotent Stem Cells -- 5. The Effects of Ageing on Proliferation Potential, Differentiation Potential and Cell Surface Characterization of Human Mesenchymal Stem Cells -- 6. GMP Grade Mesenchymal Stem Cell Culture for Clinical Usages -- 7. Isolation and Characterization of Adipose Derived Stromal/Stem Cells -- 8. Cord Blood Stem Cell Banking -- 9. Human Embryonic Stem Cells and Associated Clinical Concerns -- 10. Harvesting and Collection of Adipose Tissue for the Isolation of Adipose Derived Stromal/Stem Cells -- Index.
Keywords: Life sciences; Stem Cells; Regenerative Medicine